PENGARUH PENERAPAN MODEL LEARNING AKTIVITY AND DEVELOPMENT DALAM PEMBELAJARAN BOLA BASKET TERHADAP PENGEMBANGAN TANGGUNGJAWAB SISWA - Rajip Mustafillah Rusdiyanto (Universitas Majalengka, 2017)
AbstractThis study aims to determine how the influence of the application of learning activity and development models in basketball learning towards the development of students' responsibility in SMA Negeri 22 bandung. The study was conducted using the quasi experiment method which was conducted on 40 students (20 students who participated in the application of learning activity and development models in basketball learning), (20 students who did not participate in the application of learning activity and development models in basketball learning) who came from high school Negeri 22 Bandung. Data were collected using student responsibility questionnaires, all data were analyzed using (1) testing instrument validity (2) instrument reliability testing (3) calculating means and standard deviations (4) normality tests (5) homogeneity tests (6) tests hypothesis with the help of Windows SPSS Program version 17. The results of data analysis show that the level of responsibility of students who take part in implementing learning activity and development models in basketball learning is 83.96. Based on the results of the independent sample test it was proven that there was a significant influence between the application of the learning activity and development model in basketball learning. While the homogeneity test results proved that there was a homogeneous correlation between learning model learning activity and development of learning basketball) originating from high school Negeri 22 Bandung towards developing effective student responsibility of 3,864. This means that students who take part in implementing learning activities of learning and development models affect the development of student responsibilityKeyword: Learning Activity and Development Model, Responsibility, Physical Education. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana pengaruh penerapan model learning activity and development dalam pembelajaran bola basket terhadap pengembangan tanggungjawabsiswa SMA Negeri 22 bandung. Penelitian dilakukan dengan menggunakan metode quasi experimentsyang dilakukan terhadap 40 orang siswa (20 siswa yang mengikuti penerapan model learning activity and development dalam pembelajaran bola basket), (20 siswa yang tidak mengikuti penerapan model learning activity and development dalam pembelajaran bola basket) yang berasal dari SMA Negeri 22 Bandung. Data dikumpulkan dengan menggunakan angket tanggung jawab siswa, semua data di analisis menggunakan (1) pengujian validitas intrumen (2) pengujian reliabilita instrument (3) menghitung rata-rata dan simpangan baku (4) uji normalitas (5) uji homogenitas (6) uji hipotesis dengan bantuan Program SPSS Windows versi 17. Hasil analisis data menunjukan bahwa tingkat tanggung jawab siswa yang mengikuti kegiatan penerapan model learning activity and development dalam pembelajaran bola basket 83,96. Berdasarkan hasil uji- independen sample test terbukti bahwa adanya pengaruh yang signifikan antara penerapan model learning activity and development dalam pembelajaran bola basket.sedangkan hasil uji-homogenitas terbukti ada korelasi yang homogen antara pembelajaran model learning activity and development pembelajaran bola basket) yang berasal dari SMA Negeri 22 Bandung terhadap pengembangan tanggungjawab siswa yang efektif sebesar 3,864. Artinya siswa yang mengikuti kegiatan penerapan pembelajaran model learning activity and development berpengaruh terhadap pengembangan tanggungjawab siswa.Kata Kunci: Model Learning Activity and Development, Tanggungjawab, Pendidikan Jasmani